Ergostane steroids from Aspergillus sp. M904 in Vietnam - Trinh, Thi Thanh Van; Nguyen, Mai Anh; Vu, Van Nam; Nguyen, Thuy Linh; Le, Thi Hong Minh; Murphy, Brian T.; Doan, Thi Mai Huong; Pham, Van Cuong (Vietnam Journal of Marine Science and Technology, 2024)
Seven ergostane steroids were isolated from the cultures of Aspergillus sp. M904, an endophytic fungus isolated from the marine sediment sample collected at a depth of ten meters in Binh Dinh, Vietnam. These compounds include 5α,6α-epoxy-(22E,24R)-ergosta-8(14),22-diene-3β,7α-diol (1), 5α,6α-epoxy-(22E,24R)-ergosta-8(9),22-diene-3β,7α-diol (2), ergosterol (3), ergosterol peroxide (4), 3β,5α,6α-trihydroxy-ergosta-7,22-diene (5), 3β,5α,9α-trihydroxy-ergosta-7,22-diene-6-one (6), 3β-hydroxy-5α,9α-epoxy-ergosta-7,22-dien-6-one (7). Their structures were identified through MS and NMR data analyses. All compounds were evaluated for their antimicrobial activity against a panel of clinically significant microorganisms. Compounds 1–7 had inhibitory activity against from one to six tested strains with MIC values from 64–256 µg/mL.